Analysis of curing behavior of endo-dicyclopentadiene using different amounts of decelerator solution. (15th March 2019) - Yoo, Hyeong Min; Jeon, JI Ho; Li, Mei-Xian; Lee, Woo Il; Choi, Sung Woong
Abstract: The curing kinetics of endo-dicyclopentadiene (endo-DCPD) was analyzed using isothermal differential scanning calorimetry by experimentally acquiring kinetic parameters according to model fitting approaches. To investigate the effect of the decelerator, the curing kinetics of endo-DCPD with different amounts of decelerator solutions was also examined. The result of the developed model was in good agreement with the experimental data. The results showed that the decelerator had an effect on the delay of a reaction process and slowed down the curing process. The impact properties of glass fiber reinforced polydicyclopentadiene (p-DCPD) with different amounts of decelerator solutions were evaluated and compared with that of the glass fiber reinforced p-DCPD to investigate the effect of the decelerators. The impact energy was shown to decrease with increasing wt. % of decelerators from 0.5 wt % to 2.0 wt % with values from 10.75 to 15.89%, respectively. Highlights: The curing kinetics of endo-DCPD based on isothermal DSC experimental data was investigated. Curing kinetics model was developed by experimentally obtained kinetic parameters based on the model fitting methods. Decelerator effect was examined using different amounts of decelerator solutions. The curing kinetics of the endo-DCPD using different amounts of decelerator solutions was verified. Impact properties for the glass fiber reinforced polydicyclopentadiene (p-DCPD) were evaluated and compared with p-DCPD with different amounts of decelerator solutions.